2016
DOI: 10.1002/pop4.127
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Young Women in Rural Western Kenya on Unconditional Cash Transfers

Abstract: Unconditional cash transfers (UCTs) provide money to eligible individuals, without dictating how they spend the money or tasks they must do to receive it. This study explored how UCTs affected the lives of young, impoverished women in rural western Kenya. Qualitative methods were used, including in‐depth interviews with 30 women: 10 receiving $1,000, 10 receiving $500, and 10 not receiving a UCT. UCTs were positively viewed by interviewees, and had nuanced and varied effects on aspirations, money management, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Providing food vouchers instead of checks would eliminate the other useful and healthy ways recipients used this additional income. Junior et al also found study participants preferred cash because “they could decide how to use [unconditional cash transfers] to meet their unique needs.” 43…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing food vouchers instead of checks would eliminate the other useful and healthy ways recipients used this additional income. Junior et al also found study participants preferred cash because “they could decide how to use [unconditional cash transfers] to meet their unique needs.” 43…”
Section: Discussionmentioning
confidence: 99%
“…Some recipients also raised this as a concern, and thought that even small increases ($5-$20/month) would make a difference. Although there is limited evidence related to the amount of money provided to recipients through unconditional cash transfers, a study in Kenya compared the perspectives of women receiving an unconditional cash transfer of $1000 with those receiving $500, and found those who received less money “were more likely to say nothing good had happened in their life.” 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cash transfers may enable beneficiaries to pay for higher quantity and quality of food as well as curative and preventative health visits, transportation to health facilities, and medical supplies. However, beneficiary spending of cash transfers does not happen in a vacuum, but is influenced by individual beliefs, attitudes and relationships to other household members (Zembe-Mkabile et al, 2018; Scott et al, 2017; Tonguet-Papucci et al, 2017; Junior et al, 2016). These influences are frequently the target of complementary behaviour change components (Molyneux and Thomson, 2011; Attanasio et al, 2009; Barca et al, 2015; Robertson et al, 2014; Adato and Hoddinott, 2010), but their mechanism of operation remains little explored.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that husbands in poverty retain the major decision-making power over the allocation of money and that women are relegated to making decisions only about small household purchases. Junior, Katz, and Ahn's (2016) qualitative study found that, when asked about household money management, impoverished married women most often responded that their husbands had the final say about financial decisions. Silva-Segovia and Lay-Lisboa's (2017) study also revealed that money has meaning as a symbolic element of power.…”
Section: Introductionmentioning
confidence: 99%